Experimental murine model of neurocysticercosis: first report of cerebellum as a location for Mesocestoides corti tetrathyridia - Fabbri, Julia (2018)
Neurocysticercosis is a parasitic disease caused for encysted larvae of Taenia solium in human central nervous system. Cysts mainly affect cerebral hemispheres, although they can also be found in ventricles, basal cisterns, and subarachnoid spaces, rarely in cerebellum. Due to the impossibility to study the disease in human patients, Cardona et al. (1999) developed a mice model of neurocysticercosis, using Mesocestoides corti, a closely related cestode. This allows us to study the parasite-host relationship and the mechanisms involved in the disease, in order to improve the therapy. In this murine model of neurocysticercosis, the location of tetrathyridia in parenchyma, ventricles and meninges has already been reported. The aim of this work was to report the cerebellum as a new location for M. corti tetrathyridia in the murine model of neurocysticercosis. A murine model that reproduces the human pathology is essential to evaluate the symptomatology and response to drug treatment in experimentally infected mice.